2014
DOI: 10.1172/jci75938
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous intrahepatic IFNs and association with IFN-free HCV treatment outcome

Abstract: BACKGROUND. Hepatitis C virus (HCV) infects approximately 170 million people worldwide and may lead to cirrhosis and hepatocellular carcinoma in chronically infected individuals. Treatment is rapidly evolving from IFN-α-based therapies to IFN-α-free regimens that consist of directly acting antiviral agents (DAAs), which demonstrate improved efficacy and tolerability in clinical trials. Virologic relapse after DAA therapy is a common cause of treatment failure; however, it is not clear why relapse occurs or whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
200
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(236 citation statements)
references
References 50 publications
34
200
1
1
Order By: Relevance
“…As type I IFN has been shown to negatively control pDC numbers in various in vitro infection models, it was thus suggested that type I IFN might negatively regulate pDC numbers during HCV infection. A recent immunohistochemistry analysis in fact failed to detect any pDCs both in pretreatment and end-of-treatment human liver biopsies [40]. …”
Section: Induction Of Ifns and Isgs In Chronic Hcv Infection: The LIVmentioning
confidence: 99%
“…As type I IFN has been shown to negatively control pDC numbers in various in vitro infection models, it was thus suggested that type I IFN might negatively regulate pDC numbers during HCV infection. A recent immunohistochemistry analysis in fact failed to detect any pDCs both in pretreatment and end-of-treatment human liver biopsies [40]. …”
Section: Induction Of Ifns and Isgs In Chronic Hcv Infection: The LIVmentioning
confidence: 99%
“…Similar studies showed that the rapid decline of HCV viral load by DAAs was associated with restored HCV specific memory T cell dedifferentiation, lymphocyte deactivation and normalized natural killer cell function [42][43][44]. Mir-122, which plays a central role in orchestrating hepatocarcinogenesis was recently found to be decreased in serum samples after IFN-free therapy [45]. IFN-free therapy leads to the downregulation of type II and III IFNs, their receptors and IFN stimulated genes [46].…”
Section: Molecular Mechanisms Of Hcc Occurrence or Recurrence With Damentioning
confidence: 84%
“…HLA-A*0201-restricted HCC-specific peptides of AFP [137][138][139][140][141][142][143][144][145] (PLFQVPEPV), NY-ESO-1 157-165 (SLLMWITQC), MAGE-A3 112-120 (KVAELVHFL), MAGE-A10 [254][255][256][257][258][259][260][261][262] (GLYDGMEHL), SSX-2 [41][42][43][44][45][46][47][48][49] (KASEKIFYV) and p53 [149][150][151][152][153][154][155][156][157] (STPPPGTRV) at purities ranging from 82.78 to 97.99% were also obtained from ProImmune Ltd. For these HCC-associated epitope-specific peptides, corresponding PE-labeled MHC class I dextramers were obtained from Immudex (Copenhagen, Denmark). Further, HBV-specific 15-mer overlapping peptides covering the core (4 pools from 41 peptides) and polymerase regions (8 pools from 165 peptides) were purchased from ProImmune Ltd. Also, HLA-A*0201-restricted HBV-specific peptides Core [18][19][20][21][22][23][24][25][26][27] (FLPSDFFPSV), Env [183][184][185][186][187][188]…”
Section: Peptides Hla Class I Multimers and Recombinant Proteinsmentioning
confidence: 99%
“…PBMC from cirrh-to-No HCC patients (n = 17) isolated at TS, EOT, and FU were stimulated with the specific peptides in vitro. HBVspecific Core [18][19][20][21][22][23][24][25][26][27] , Env [183][184][185][186][187][188][189][190][191] , Pol 578-581 , and Surf 185-194 control peptide stimulations were used in selected patients with no HBV coinfection to secure the quality of staining (see online suppl. Fig 7).…”
Section: The Strength Of Hcc Epitope-specific Cd8+ T Cell Responses Dmentioning
confidence: 99%
See 1 more Smart Citation